Home telework, travel behavior, and land-use patterns: A path analysis of British single-worker households - de Abreu e Silva, João; Melo, Patricia C. (Journal of Transport and Land Use, 2018)
This work analyzes the effects of home-based teleworking on the number of trips and weekly miles travelled by mode and purpose for one-worker households in Great Britain using data from the National Travel Survey for the period between 2005 and 2012. Two path analysis models are developed, one considering weekly trips and travel distances by mode and the other weekly trips and travel distances by purpose. Both models consider teleworking frequency in the context of home and workplace land-use characteristics, commuting distance, car ownership levels and weekly trips and travel distances. This framework allows us to explicitly model endogenous relations in the chains of decisions relating these variables. The results suggest that home-based teleworking is a strategy used by people to cope with long and costly commutes. Workers living in less transit accessible areas and with longer commutes tend to work from home more frequently. The main conclusions relating to teleworking frequency point to the fact that it increases weekly miles travelled, particularly by car, while it does not reduce commuting distances travelled. These results suggest that home-based teleworking is not an effective travel demand management strategy, particularly because it seems to increase car use. The overall main result is that teleworkers travel more by more polluting transport modes.